Comparison of the Effectiveness of Tramadol and Dexmedetomidine as Adjuvants in Spinal Anesthesia for Prolonging Postoperative Analgesia in Patients Undergoing Hysterectomy (TAH & Vaginal Hysterectomy): Tramadol and Dexmedetomidine for Prolonging Postoperative Analgesia in Hysterectomy - Asghar, Hafiz Faheem; Bashir, Munazzah; Sabir, Sara; Ashfaq, Shumaila; Kalsoom, Zahida; Shahid, Namra; Taj, Serena (Pakistan Journal of Health Sciences, 2025)
TAH is a major procedure with significant postoperative pain, managed through various anesthetic techniques. Intrathecal dexmedetomidine offers consistent, opioid-sparing analgesia, whereas tramadol provides analgesic and anti-shivering effects but shows more variable and less established efficacy. Objectives: To evaluate the effectiveness of dexmedetomidine and tramadol in spinal anesthesia for extending postoperative analgesia in hysterectomy. Methods: A quasi-experimental study was conducted at M. Islam Medical and Dental College Teaching Hospital on two equal groups of 110 elective hysterectomy patients who were randomly assigned. Group T was given tramadol, and Group D was given dexmedetomidine. Clinical and demographic baselines were documented. Time to first rescue analgesia and total rescue analgesic intake were the main results. Patient satisfaction, incidence of adverse effects, and postoperative pain intensity were evaluated at multiple intervals. Data analysis was conducted by SPSS version 26.0 with statistical significance set at p<0.05. Results: The dexmedetomidine group’s patients consumed less rescue analgesic overall (p<0.001) and had a considerably longer duration to initial rescue analgesia (p<0.001) than the tramadol group. Additionally, the dexmedetomidine group had considerably higher patient satisfaction (p=0.002). At every time point, the dexmedetomidine group’s VAS pain scores were consistently lower (p<0.001). There was no discernible difference in the frequency of side effects between the groups. Conclusions: Dexmedetomidine resulted in improved postoperative pain control and greater patient satisfaction and reduced analgesic consumption compared to tramadol, with a comparable safety profile. It represents an effective option for multimodal postoperative pain management following hysterectomy.